2003
DOI: 10.1016/s0378-1097(03)00612-8
|View full text |Cite
|
Sign up to set email alerts
|

Two phenotypically compensating isocitrate dehydrogenases inRalstonia eutropha

Abstract: The tricarboxylic acid (TCA) cycle enzyme isocitrate dehydrogenase (IDH) and the glyoxylate bypass enzyme isocitrate lyase are involved in catabolism of isocitrate and play a key role in controlling the metabolic flux between the TCA cycle and the glyoxylate shunt. Two IDH genes icd1 and icd2 of Ralstonia eutropha HF39, encoding isocitrate dehydrogenase 1 (IDH1) and isocitrate dehydrogenase 2 (IDH2), were identified and characterized. Icd1 was functionally expressed in Escherichia coli, whereas icd2 was expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…The evolutionary distance between the two IDH isozymes from one bacterium reveals the complexity of the ancient IDH protein family. The phenomenon of the coexistence of two different IDH isozymes in one bacterium has been reported from previous studies . Two structurally different dimeric and monomeric types of IDH isozymes were confirmed to exist in the psychrophilic bacteria C .…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…The evolutionary distance between the two IDH isozymes from one bacterium reveals the complexity of the ancient IDH protein family. The phenomenon of the coexistence of two different IDH isozymes in one bacterium has been reported from previous studies . Two structurally different dimeric and monomeric types of IDH isozymes were confirmed to exist in the psychrophilic bacteria C .…”
Section: Discussionsupporting
confidence: 68%
“…It was revealed that the expression of the NADP + ‐specific IDH1 (48 kDa) of R . eutropha was induced by acetate, while the other NADP + ‐specific IDH2 (83 kDa) in this bacterium was constitutively expressed . Deletion of either of these two IDHs didn't affect the R .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations